Efektivitas Model Kooperatif Make A Match Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VII (Studi Pada Materi Pokok Sistem Organisasi Kehidupan) - Ekawati; Rifda Nurhikmawati Arif (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Low student learning outcomes on the topic of the Organization of Life Systems remain a challenge in junior high school science education. The abstract nature of the material requires the implementation of interactive learning models to increase student engagement and improve learning outcomes. This study aimed to determine the effectiveness of the Make a Match cooperative learning model in improving the learning outcomes of seventh-grade students at SMP Negeri 26 Makassar on the topic of the Organization of Life Systems. This study employed a Classroom Action Research (CAR) design conducted in three cycles, involving 32 students from Class VII.4 as research subjects. The instrument was a formative test consisting of 10 multiple-choice questions administered at the end of each cycle. Data were analyzed using the class mean score, learning mastery percentage, and N-Gain score. The results showed an improvement in students' learning outcomes, with the mean score increasing from 65.94 with a learning mastery percentage of 53.13% in Cycle I, to 76.56 with a mastery percentage of 75.00% in Cycle II, and reaching 80.78 with a mastery percentage of 84.38% in Cycle III. The N-Gain analysis obtained a score of 0.4818 (48.18%), which was categorized as moderate, with 2 students (6.25%) in the high category, 26 students (81.25%) in the moderate category, and 4 students (12.50%) in the low category. The findings indicate that the implementation of the Make a Match cooperative learning model is proven to improve students' learning outcomes on the topic of the Organization of Life Systems.